Usability and Accessibility of OERs and MOOCs among Students with Special Needs in Open and Distance Leaning: ahid Majeed (PJDOL, 2023)
The purpose of the study was to explore the issues and barriers in usability and accessibility of Open Education Resources and MOOCs by the students with special needs in distance learning. The study also highlighted the problems and issues faced by the designers, developers, instructors and administrators while designing, developing, offering and conducting the MOOCs and developing OERs